Analisis Kinerja Guru Bimbingan Konseling SMA/SMK di Surakarta - Zumrotul Muadzimah (Dharmas Education Journal (DE_Journal), 2022)
This study aims to reveal and describe how the actual situation in the field is related to the performance of BK teachers and their guidance, such as (a) the quality of BK service performance in schools, (b) the success of the services provided by BK teachers, (c) student responses as counselees or focus in the service program provided by BK teachers in schools. The type of research method is descriptive qualitative, with the subject of data collection taken from 48 students in SMA/SMK in the city of Surakarta. Clumping data using google from about the services of guidance and counseling teachers in high school / vocational schools in the city of Surakarta. The results of this study are the performance of counseling services in schools has been quite optimal, as evidenced by the high percentage of surveys stating that guidance counselors in schools are informative and the services provided by guidance counselors have been successful where success is evidenced by the number of students who have felt the presence of guidance counselors. .